Nurses’ feeling trusted and knowledge hiding: The role of psychological safety, felt obligation and traditionality - Lu, Guangli; Liang, Yipei; Ding, Yueming; Tang, Haishan; Zhang, Yiming; Huang, Haitao; Chen, Chaoran (Frontiers in Psychology, 2022)
Knowledge hiding is one of the dilemmas of organizational knowledge management. For nurses, knowledge hiding behavior is not conducive to improving the quality and efficiency of their work and hinders the innovation of nursing services. Based on the social exchange theory, the current study constructed a moderated mediation model by taking psychological safety and felt obligation as mediating variables, and traditionality as moderating variable, and explored the mechanism of feeling trusted affecting knowledge hiding behavior. The empirical research based on 285 nurses from China shows that feeling trusted is negative correlate with knowledge hiding behavior; feeling trusted can negatively affect knowledge hiding by enhancing psychological safety and felt obligation; traditionality can positively moderate the relationship between feeling trusted and felt obligation, and feeling trusted has a stronger positive influence on felt obligation of highly traditional nurses; traditionality has no significant moderating effect between feeling trusted and psychological safety. Theoretically, this study supplements the influencing factors of knowledge hiding, examines the complex mechanism between feeling trusted and knowledge hiding and supplements the boundary conditions for feeling trusted to play its role from the perspective of individual characteristics (i.e. traditionality). From the perspective of practical implication, this study suggests that managers should pay attention to using trust strategies to enhance subordinates' psychological safety and felt obligation, especially for highly traditional nurses, thus reducing knowledge hiding.